Components of soybean resistance to the soybean aphid, Aphis glycines Matsumura - Diaz-Montano, John (Kansas State University, 2006)
The soybean aphid, Aphis glycines Matsumura, is a pest of soybean, Glycine max (L.) Merr. Studies to find control methods were initiated in 2000 when it was first detected in the United States. Aphis glycines can reduce yields by as much as 50%, and vectors several viral diseases. Plant resistance to A. glycines is one important component of integrated control. In the first study, reproduction of A. glycines was compared on 240 soybean entries. Eleven had fewer nymphs produced compared with two susceptible checks (KS4202 and Pioneer® 95B15). Antibiosis and antixenosis were assessed in no-choice and choice tests, respectively. Nine entries showed moderate antibiosis and the other two (K1639 and Pioneer® 95B97) showed strong antibiosis and antixenosis as categories of resistance to A. glycines. In the second study, chlorophyll loss was estimated in no-choice tests on infested and uninfested leaves of KS4202. The minimum combined number to detect significant chlorophyll loss was 30 aphids confined for 10 days. Using this number, seven resistant entries found in the first study were evaluated. There was no significant chlorophyll reduction between infested and uninfested leaves of five of the resistant entries (K1621, K1639, 95B97, Dowling and Jackson). Jackson and Dowling had a significantly lower percentage loss than the susceptible checks. In the third study, assessment of feeding behavior of A. glycines was compared and recorded for 9 h on four resistant entries and KS4202. The average time needed to reach the first sieve element phase by A. glycines was 3.5 h in KS4202 while in the resistant entries it was 7.5 h, and the total duration in this phase was longer than an hour in KS4202, and only two to seven minutes in the resistant entries. These data suggest that phloem tissues in the resistant plants change feeding behavior. However, aphids first reached the xylem phase and then the sieve element phase, and the time that aphids spent ingesting xylem sap was not different among all entries; therefore, it is possible that xylem sap in the resistant entries may contain toxic substances that alter aphid behavior and restrain further activities on the sieve element phase.
Keywords: Soybean aphid; Soybean; Antibiosis; Antixenosis; Chlorophyll losses; Feeding Behavior; Host Plant Resistance; Agriculture, Agronomy (0285); Biology, Entomology (0353); Biology, Plant Physiology (0817)